Facial skin ageing: Key concepts and overview of processes - Zargaran, David; Zoller, Florence; Zargaran, Alexander; Weyrich, Tim; Mosahebi, Afshin (International Journal of Cosmetic Science, 2022)
Introduction The face is a cosmetically sensitive region where the process of ageing is most clearly manifested. With increased focus on anti-ageing and longevity, more anti-senescent treatments are being proposed despite limited evidence. This study outlines the pathways and mechanisms underpinning the biological process of ageing in the face. Methods Comprehensive searches of MEDLINE, EMBASE, Cochrane Library and CINAHL from inception to 2020. Inclusion criteria included all empirical human research studies specific to facial ageing features, written in the English language. Results A total of 65 papers met inclusion criteria for analysis. Pathways were subdivided into intrinsic and extrinsic senescence mechanisms. Intrinsic pathways included genetics, generation of reactive oxygen species and hormonal changes. Extrinsic pathways included photoageing and damage to skin layers. The combined intrinsic and extrinsic pathway alterations result in wrinkles, higher laxity, slackness and thinning of the skin. Skin functions such as barrier immune function, wound healing, thermoregulation and sensory function are also impaired. Conclusion The ageing process is unique to the individual and depends on the interplay between an individual's genetics and external environmental factors. Through understanding the molecular and cellular mechanisms, an appreciation of the consequent structural and functional changes can be achieved. Based on this knowledge, further research can focus on how to slow or impede the ageing process and identify specific targets to develop and evolve new treatment strategies.
CRIS-Team WoS Importer:2022-07-22